Co2 Emissions and Economic Growth in Vietnam: An ARDL Bound Testing Approach - NGUYEN, Nhung Thi Kim; LE, Minh Binh (Asian Journal of Economic Modelling, 2018)
This study examines the impacts of CO2 emissions on economic growth of Vietnam for the period 1986-2015 by using Autogressive Distributed Lag (ARDL) model. The results reveal that there is cointegration relationship between CO2 emissions and economic growth. In the long run carbon dioxide emissions have a significant negative impact on Vietnam economic growth. Therefore, in order to achieve a sustainable growth and development, it is advisable for the Vietnamese government to focus on environmental protection policy.